2018
DOI: 10.1111/jch.13310
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressures immediately following ischemic strokes are associated with cerebral perfusion and neurologic function

Abstract: The optimal range of blood pressure levels in the early phase of ischemic stroke with hypertension is still controversial. Based on our stroke registry database, we explored the relationship between blood pressure levels and cerebral perfusion in the early phase of ischemic stroke with hypertension and neurofunctional recovery at 3 months after stroke. Total 732 stroke patients with hypertension were finally analyzed. Patients were divided into quintiles according to systolic blood pressure (SBP) and diastolic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…8,36 A longitudinal study observed a reverse U-shaped relationship between DBP immediately following ischemic strokes and cerebral perfusion in hypertensive patients. 8 However, previous randomized controlled trials demonstrated that intensive BP control had no reduction or even improvement on cerebral perfusion, compared with standard BP control. 21,37,38 We further found no evidence that baseline DBP modified the effect of intensive BP control on CBF (interaction P =0.25).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…8,36 A longitudinal study observed a reverse U-shaped relationship between DBP immediately following ischemic strokes and cerebral perfusion in hypertensive patients. 8 However, previous randomized controlled trials demonstrated that intensive BP control had no reduction or even improvement on cerebral perfusion, compared with standard BP control. 21,37,38 We further found no evidence that baseline DBP modified the effect of intensive BP control on CBF (interaction P =0.25).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, in patients with low DBP, aggressive BP reduction raised concerns regarding possible cerebral hypoperfusion, which might potentially result in negative effects on cognitive function. 8,36 A longitudinal study observed a reverse U-shaped relationship between DBP immediately following ischemic strokes and cerebral perfusion in hypertensive patients. 8 However, previous randomized controlled trials demonstrated that intensive BP control had no reduction or even improvement on cerebral perfusion, compared with standard BP control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There was even a decrease in CBF within normal appearing white matter surrounding the WMH 51 . On the other hand, levels of cerebral perfusion especially in the early phase of AIS display a reverse U-shaped curve depending on SBP and DBP levels and -in turn -impact functional outcome at 3 months after stroke 52 . The most favorable functional outcome was associated with a SBP between 161 to 177 mmHg and DBP ranging from 103 to 114 mmHg 52 .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, levels of cerebral perfusion especially in the early phase of AIS display a reverse U-shaped curve depending on SBP and DBP levels and -in turn -impact functional outcome at 3 months after stroke 52 . The most favorable functional outcome was associated with a SBP between 161 to 177 mmHg and DBP ranging from 103 to 114 mmHg 52 . Interestingly, Park and Ovbiagele found also an independent association between DBP and vascular outcomes 2 years after non-cardioembolic stroke, showing that DBP < 70 mmHg as well as DBP > 90 mmHg was linked to an increased risk of vascular events 53 .…”
Section: Discussionmentioning
confidence: 99%